Of spiritual and natural: Revitalizing the religious and natural tourism in Sitakunda through Architecture and landscape - Mahmud, Tarannum (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2020.